2009
DOI: 10.3233/bme-2009-0578
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the dentin surface by using carbon nanotubes

Abstract: Recent studies have shown that carbon nanotubes (CNTs) can be used as biomedical materials because of their unique properties. CNTs effect nucleation of hydroxyapatite, because of which considerable interest has been generated regarding the use of CNTs in dentistry. However, there are only a few reports on the use of CNTs as dental materials. In this study, we investigated the changes induced in the surfaces of tooth slices by the application of a coating of CNTs by observing CNTcoated tooth slices both macros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…44 In our study, the inclusion of CNPs inside the adhesives also improved their bond strength (although less than the 2.5% GNP adhesive), and our results agree with the findings of a similar previous study. 24 CNPs interact and adhere selectively with the collagen fibers of dentin, 13,14 and this could have probably resulted in improving the bond strength of the adhesive, as seen in the current study. Most of the failures detected in the present study were adhesive in nature.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…44 In our study, the inclusion of CNPs inside the adhesives also improved their bond strength (although less than the 2.5% GNP adhesive), and our results agree with the findings of a similar previous study. 24 CNPs interact and adhere selectively with the collagen fibers of dentin, 13,14 and this could have probably resulted in improving the bond strength of the adhesive, as seen in the current study. Most of the failures detected in the present study were adhesive in nature.…”
Section: Discussionmentioning
confidence: 53%
“…10 In dentistry, CNPs have been used for drug delivery and reinforcing restorative materials due to their apt biocompatibility and superior mechanical strength. 11,12 Previously, it was shown in a study that CNPs could adhere selectively with the collagen fibers of dentin, 13 and this could possibly boost mechanical strength of the adhesives. Suo et al also indicated that CNPs intermingle with the collagen fibers, forming a firm surface coating on dentin.…”
Section: Introductionmentioning
confidence: 99%
“…Nanotubes can induce inflammatory and fibrotic reactions under some conditions by crossing membrane barriers. [98][99][100][101][102] Graphene Teeth coating, suitable for implantation, biofilm reduction Cost effectiveness, fracture resistant, low density form a uniform crystal lattice, treat bacterial biofilm…”
Section: Carbon Nanotubesmentioning
confidence: 99%
“…Akasaka et al coated the dentin surface with CNTs solution aimed at prevention of recurrent caries under composite restoration. The authors observed that CNTs could serve as promising pre-treatment agents under composite restoration, since they were found to bond to the collagen of dentin, serves as nucleation sites for hydroxyapatite without interfering the bond strength of composite to tooth [37]. The strength and stiffness of composite and epoxy resin were increased by incorporation of CNTs which acted as nanollers [38].…”
Section: Carbon Nanotubesmentioning
confidence: 99%